Gather volunteers to prepare PPE equipments - UMP, PNC (2020)
Kuantan, 5 May 2020 - Recognizing the need for self-protective clothing (PPE) for the current use of the Ministry of Health (MOH) personnel and ongoing demand for PPE has inspired the staff of UMP Services Sdn. Bhd. (USSB) a subsidiary of UMP Holdings Sdn. Bhd. to gather volunteers to assist in the preparation of this PPE equipment.